AKUNTABILITAS DAN DISFUNGSI ORGANISASI DALAM PENYUSUNAN RPJMDES: STUDI KASUS DESA SUMBER KETEMPA - Nahrudi Nahrudi; Sonia Ariani Pratiwi; Emilia Ananta; Cindi Saputri; Oryza Ardhiarisca (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study employs a qualitative, case-based method to explore the reasons and ways in which accountability and organizational dysfunction impact the performance of the team developing the Village Medium-Term Development Plan (RPJMDes) in Sumber Ketempa Village, Kalisat District, Jember Regency. The delay in completing the revised RPJMDes until the end of 2025 indicates a low level of team performance. Through in-depth interviews, observations, and document analysis, this study uncovered moral hazard (the division of responsibilities among Village Operators) and adverse selection (a weak internal control system) as manifestations of the failure to implement Agency Theory at the village government level. Organizational dysfunction is evident in weak coordination, conflicting priorities due to an emphasis on short-term programs (such as stunting), and excessive reliance on a single individual. This collective failure has led to the delay of Village Deliberations and hampered the development of follow-up documents (RKPDes and APBDes). Therefore, strengthening the accountability system, consistency in coordination, and effective oversight are needed to ensure the achievement of village development planning objectives.